Transfer Of Knowledge Through The Lens Of rganizational Culture: A Literature Review - Shabana Gul; Dr. Waseef Jamal; Dr. Waseef Jamal (Journal of Business & Tourism, 2021)
This study aims to summarize the possible relationship between the transfer of knowledge and organizational culture and highlight the empirical relevance between them. For this purpose, a literature review of 169 articles (both qualitative and quantitative studies) has been conducted that have attempted to provide evidence of their relationship. Future empirical research suggestions for understanding the relationship between organizational culture and transfer of knowledge are also provided